DAYA TARIK WISATA TERHADAP KEPUASAN WISATAWAN OBJEK WISATA BENTENG ROTTERDAM KOTA MAKASSAR - Muhammad Arhan Rajab (Pringgitan, 2020)
This study aims to determine whether there is an influence between the development of tourist objects on tourist satisfaction at the tourist attraction of Fort Rotterdam in Makassar City. This research was conducted at the tourist attraction of Fort Rotterdam, the population of which was all visitors who visited in 2019, amounting to 2,350 people. To determine the sample to be the respondent is determined by the Slovin formula so that the sample is 96 tourists, while the data collection techniques used questionnaires and interviews, while the data analysis used the statistical product moment correlation with the rough number formula (rXY). The results of data analysis show that the influence of tourism development on tourist satisfaction has a strong correlation, indicated by the correlation coefficient r count of 0.782 in fact> (greater) than r table of 0.195 at a significant level of 5% and 0.254 at a significant level of 1%. The results of the calculation of the coefficient of determination show that the Tourism Object Development variable (X) has an effect of 78.2% on the tourist satisfaction variable (Y), while the remaining 21.8% is influenced by other variables which are not investigated in this study.Keywords: Satisfaction, Tours, Rotterdam Fort, Makassar City